Highly purified extracellular vesicles from human cardiomyocytes demonstrate preferential uptake by human endothelial cells. Issue 38 (24th September 2020) - Zwi-Dantsis, Limor; Winter, Charles W.; Kauscher, Ulrike; Ferrini, Arianna; Wang, Brian; Whittaker, Thomas E.; Hood, Steve R.; Terracciano, Cesare M.; Stevens, Molly M.
Abstract : Highly purified EVs isolated from human cardiomyocytes show differential uptake in cardiac cell types. Abstract : Extracellular vesicles (EVs) represent a promising cell-free alternative for treatment of cardiovascular diseases. Nevertheless, the lack of standardised and reproducible isolation methods capable of recovering pure, intact EVs presents a significant obstacle. Additionally, there is significant interest in investigating the interactions of EVs with different cardiac cell types. Here we established a robust technique for the production and isolation of EVs harvested from an enriched (>97% purity) population of human induced pluripotent stem cell (iPSC)-derived cardiomyocytes (CMs) with size exclusion chromatography. Utilizing an advanced fluorescence labelling strategy, we then investigated the interplay of the CM-EVs with the three major cellular components of the myocardium (fibroblasts, cardiomyocytes and endothelial cells) and identified that cardiac endothelial cells show preferential uptake of these EVs. Overall, our findings provide a great opportunity to overcome the translational hurdles associated with the isolation of intact, non-aggregated human iPSC-CM EVs at high purity. Furthermore, understanding in detail the interaction of the secreted EVs with their surrounding cells in the heart may open promising new avenues in the field of EV engineering for targeted delivery in cardiac regeneration.